REDUCED RENAL GLOMERULAR FILTRATION AND SHORT- AND LONG-TERM PROGNOSIS IN PATIENTS AFTER CORONARY ARTERY BYPASS GRAFT SURGERY - B. G. Iskenderov; O. N. Sisina (Российский кардиологический журнал)
Aim. To identify the risk factors and clinical features of acute kidney injury (AKI) in patients with chronic kidney disease (CKD) who underwent coronary artery bypass graft surgery (CABG); to assess the impact of reduced renal glomerular filtration on the short- and long-term prognosis in these patients.Material and methods. The study included 487 patients (294 men and 193 women) aged 45-68 years (mean age 58,0±7,6 years), who underwent planned CABG. Before the intervention, CKD was registered in 330 patients (Group 1), while in 157 patients, no clinical, laboratory, or instrumental evidence of CKD was observed (Group 2). AKI within the first 24 hours after CABG was diagnosed according to the RIFLE criteria (serum creatinine levels). The follow-up period was 3 years after CABG. Results. In the early post-intervention period, Group 1 developed AKI significantly more often than Group 2: 59,4% vs. 25,1%, respectively (p<0,001). The main risk factors of AKI were arterial hypertension (AH), Type 2 diabetes mellitus, congestive chronic heart failure (CHF), and persistent atrial fibrillation for Group 1 and AH and congestive CHF for Group 2. Moreover, Group 1, in contrast to Group 2, was characterised by moderate and severe AKI, as well as by persistent and irreversible AKI. In-hospital lethality was higher for Group 1 than for Group 2 (16,1% vs. 6,0%, respectively; p<0,001), although this difference in AKI patients was not statistically significant (21,4% for Group 1 vs. 15,3% for Group 2; p>0,05). In patients with preexisting CKD (Group 1), 3-year survival was significantly lower than in Group 2 patients, irrespective of AKI development (p<0,001).Conclusion. Reduced renal glomerular filtration affects both short- and long-term prognosis after CABG and increases the risk of AKI.